Hepatic Abscess due to Streptococcus anginosus and Eikenella corrodens, Secondary to Gastric Perforation by a Fish Bone - Gonçalves,Rita João (2019)
Introduction: Foreign-body ingestion is a common event, but in only less than 1% of the cases complications occur. Hepatic abscesses induced by foreign-body penetration are rare. To date, there are only 62 reported cases of hepatic abscess secondary to fish bone perforation of the gastrointestinal tract. Case Presentation: A 78-year-old male patient was admitted due to high fever and vomiting for 2 days, along with frequent eructations for the past 3 months. Abdominal ultrasound showed a liver abscess in the left lobe, and computed tomography revealed a hyperdense linear image that crossed the superior wall of the gastric antrum, contacting the liver lesion, suggestive of a foreign body, probably a fish bone. Blood cultures were positive with isolation of Streptococcus anginosus and Eikenella corrodens. Ultrasound-guided percutaneous drainage of the abscess was done, and S. anginosus was isolated in the pus. Surgical debridement and fish bone removal were performed; the patient completed 21 days of antibiotic therapy, with a favourable evolution. Conclusion: To the best of our knowledge, this is the first reported case of liver abscess caused by fish bone penetration with isolation of S. anginosus and E. corrodens. Bacterial coaggregation is one of the mechanisms that can explain their ability for causing invasive infections away from the oral cavity, by increasing their resistance to the innate immune system and survival of both species.